Saxifraga kegangii (Saxifragaceae), a new species from Hunan province of central China - Zhang, Meng-Hua; Zhang, Xiao-Shuang; Nie, Ze-Long; Zhang, Dai-Gui; Meng, Ying (Phytotaxa, 2017)
Saxifraga kegangii, a new species of Saxifraga sect. Irregulares (Saxifragaceae) from Hunan province of central China, is described and illustrated. This new species can be easily distinguished from related taxa by its leaf shape and disc semiannular around the side of the ovary. Placement of this species within Saxifraga sect. Irregulares is assessed based on molecular phylogenetic analysis of the nuclear ribosomal ITS and two chloroplast regions (trnL-F and psbA-trnH) sequences together with morphological comparisons.